Longitudinal study on Streptococcus pneumoniae, Haemophilus influenzae and Staphylococcus aureus nasopharyngeal colonization in HIV-infected and -uninfected infants vaccinated with pneumococcal conjugate vaccine. Issue 23 (28th May 2015) - Madhi, Shabir A.; Izu, Alane; Nunes, Marta C.; Violari, Avye; Cotton, Mark F.; Jean-Philippe, Patrick; Klugman, Keith P.; von Gottberg, Anne; van Niekerk, Nadia; Adrian, Peter V.
Abstract: Background: Streptococcus pneumoniae, Haemophilus influenzae and Staphylococcus aureus are all potentially pathogenic, which frequently colonize the nasopharynx (NP) prior to causing disease. We studied bacterial NP-colonization in 321 HIV-infected and 243 HIV-uninfected children vaccinated with 7-valent pneumococcal conjugate vaccine (PCV7) at 6, 10 and 14 weeks of age. Methods: HIV-uninfected infants included those born to HIV-uninfected (HUU) and HIV-infected women (HEU); HIV-infected children with CD4+ lymphocyte ≥25% were randomized to initiate antiretroviral therapy immediately (ART-Immed) or when clinically indicated (ART-Def). Nasopharyngeal swabs for bacterial culture were taken prior to each PCV7 dose (Visits 1–3) and at 20, 39, 47 and 67 weeks of age (Visits 4–7). Swabs were cultured by standard methods and pneumococcal serotyping done by the Quellung method. Results: Colonization patterns for pneumococcus, H. influenzae and S. aureus did not differ between HUU and HEU children; and were also generally similar between ART-Def and ART-Immed children. Prevalence of PCV7-serotype colonization was similar between HIV-infected and HIV-uninfected children, however, overall pneumococcal and specifically non-vaccine serotype colonization tended to be lower in HIV-infected children. HIV-infected children also had a 44% lower prevalence of S. aureus colonization at Visit-1 ( p  = 0.010); and H. influenzae colonization was also lower among HIV-infected than HIV-uninfected children at Visit-2, Visit-3, Visit-6 and Visit-7. Conclusion: Vaccine-serotype colonization is similar in PCV-immunized HIV-infected and HIV-uninfected children. We, however, identified a lower prevalence of overall-pneumococcal and H. influenzae colonization in HIV-infected children post-PCV vaccination, the clinical-relevance of which warrants further study.